Effects of the Central Density Profile and the Stellar Mass Function of Merging Galaxies on Eccentricities and Coalescence Times of Supermassive Black Hole Binaries. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Khan, Fazeel Mahmood; Berczik, Peter; Just, Andreas
Abstract: If able to coalesce in a Hubble time, Supermassive Black hole (SMBH) binaries are very promising sources of gravitational waves (GW). Our earlier studies have shown that SMBH binaries coalesce in post-merger galactic nuclei having triaxial or axisymmetric geometry in a few billion years. In this study, we model the complete evolution of SMBH binaries formed as a result of galaxy mergers having central density profiles that vary from shallow to very steep including a stellar mass function. Energy and angular momentum loss due to GW emission is taken into account using the post-Newtonian approximation. We carry out ten such simulations for each central density profile. The eccentricity of the SMBH binaries remain very high in shallow cusps and decrease systematically for steeper cusps. The coalescence times range from 0.6 to 1.5 Gyr with shorter times for steeper profiles. Typical coalescence times less than a Gyr strengthen our expectation that SMBH binaries should be very promising sources of GW radiation over a wide redshift range.